Novel strategies to overcome tumor immunotherapy resistance using CAR NK cells - Guo, Jun-Hui; Afzal, Ali; Ahmad, Sadia; Saeed, Ghazala; Rehman, Amna; Saddozai, Umair Ali Khan; Liu, Lei; Guo, Shi-Hao; Ji, Xin-Ying; Khawar, Muhammad Babar (Frontiers in Immunology, 2025)
While immunotherapy faces obstacles, the emergence of chimeric antigen receptor (CAR) engineered natural killer (NK) cells is paving new ways and might become a preferred option over CAR T cells very soon. CAR NK introduce diverse cytotoxic mechanisms offering novel strategies to combat tumor immunotherapy resistance. Concurrently, improvements in NK cell homing and gene-edited CAR NK cell therapy offer promising avenues for overcoming challenges in cancer immunotherapy. Our review addresses resistance mechanisms and engineering strategies to enhance CAR NK cell functionality by improving NK cell homing and migration to tumor sites, emphasizing insights from preclinical and clinical studies.